A fundamental study of copper and cyanide recovery from gold tailings by sulfidisation - Simons, Andrew Murray (Curtin University, 2015)
Cyanide soluble copper in gold ores causes numerous problems for gold producers using cyanidation. This includes increased costs from high cyanide consumption and a requirement to destroy cyanide in the tailings before discharge into a tailings storage facility. This thesis details the results of fundamental studies of sulfidisation processes, such as SART (sulfidisation, acidification, recycle, and thickening), to recycle cyanide and in turn recover copper from gold cyanidation tailings.